Paving the way while playing catch up: mitochondrial genetics in African ancestry primary open-angle glaucoma - Kuang, Grace; Salowe, Rebecca; O’Brien, Joan (Frontiers in Ophthalmology, 2023)
Glaucoma, the leading cause of irreversible blindness worldwide, disproportionately affects individuals of African descent. Specifically, previous research has indicated that primary open-angle glaucoma (POAG), the most common form of disease, is more prevalent, severe, early-onset, and rapidly-progressive in populations of African ancestry. Recent studies have identified genetic variations that may contribute to the greater burden of disease in this population. In particular, mitochondrial genetics has emerged as a profoundly influential factor in multiple neurodegenerative diseases, including POAG. Several hypotheses explaining the underlying mechanisms of mitochondrial genetic contribution to disease progression have been proposed, including nuclear-mitochondrial gene mismatch. Exploring the fundamentals of mitochondrial genetics and disease pathways within the understudied African ancestry population can lead to groundbreaking advancements in the research and clinical understanding of POAG. This article discusses the currently known involvements of mitochondrial genetic factors in POAG, recent directions of study, and potential future prospects in mitochondrial genetic studies in individuals of African descent.